GENE EDITING: THE BOUNDARIES OF HUMAN MORALITY - Amrit Kaur Sidhu (International Educational Journal of Science and Engineering, 2024)
Revolutionary advancements in gene editing, particularly CRISPR-Cas9 technology, hold immense potential for curing genetically mutated diseases and enhancing human characteristics. However, these developments raise significant ethical concerns about societal implications and the preservation of humanity. The increasing presence of gene editing technologies has sparked intense debates about the moral ramifications of human-driven genetic engineering, including embryo experimentation and social inequality due to limited accessibility. While extensive research has highlighted CRISPR-Cas9’s capabilities and associated risks, recent controversial cases have intensified ethical discussions. Addressing these moral challenges is essential to uphold morality and prevent the misuse of such transformative tools. Through case studies, regulatory frameworks, and philosophical perspectives, the scientific community and various organizations have shaped this critical discourse on the appropriate use of genome modification. Contributing to these ongoing discussions, this paper explores the societal dangers and ethical implications of gene editing for future generations, emphasizing the responsibility required to prevent unintended consequences. Ultimately, it provides a comprehensive overview of the factors influencing the morality of genetic modifications and underscores the need for strict regulations to safeguard individuality.